Catalytic activation of small molecules - Aslan, Mustafa Yasin; Daisley, Angela; Hargreaves, Justin S J.; Rico, José L. (RSC catalysis series, 2025)
Small molecule activation encompasses various catalytic processes which are currently conducted on the industrial scale, such as steam reforming of methane and ammonia synthesis, and which are of tremendous global importance. In addition to this, there are a number of interesting, and potentially societally transformative, target reactions such as the valorisation of carbon dioxide. Providing a state-of-the-art account of the area of small molecule activation this book brings together some of the challenges and approaches to catalytic activation of methane, nitrogen, carbon monoxide and carbon dioxide. Discussing a mixture of currently operated industrial processes and highly desirable target reactions using heterogeneous catalysis, electrocatalysis, photocatalysis and chemical looping approaches it is a valuable resource for academics and industrial researchers alike.